Quality Management Framework for Total Diet Study centres in Europe. (1st February 2018) - Pité, Marina; Pinchen, Hannah; Castanheira, Isabel; Oliveira, Luisa; Roe, Mark; Ruprich, Jiri; Rehurkova, Irena; Sirot, Veronique; Papadopoulos, Alexandra; Gunnlaugsdóttir, Helga; Reykdal, Ólafur; Lindtner, Oliver; et al.
Highlights: Development of Quality Management Framework for Total Diet Studies. Total Diet Study planning phase processes. Total Diet Study practical phase processes. Standard Operating Procedures for Total Diet Studies. Peer review of pilot Total Diet Studies. Abstract: A Quality Management Framework to improve quality and harmonization of Total Diet Study practices in Europe was developed within the TDS-Exposure Project. Seventeen processes were identified and hazards, Critical Control Points and associated preventive and corrective measures described. The Total Diet Study process was summarized in a flowchart divided into planning and practical (sample collection, preparation and analysis; risk assessment analysis and publication) phases. Standard Operating Procedures were developed and implemented in pilot studies in five organizations. The flowchart was used to develop a quality framework for Total Diet Studies that could be included in formal quality management systems. Pilot studies operated by four project partners were visited by project assessors who reviewed implementation of the proposed framework and identified areas that could be improved. The quality framework developed can be the starting point for any Total Diet Study centre and can be used within existing formal quality management approaches.